Foreign Direct Investment: A Key Driver for Achieving Viksit Bharat by 2047 - Verma, Renu; Agrawal, Alok (Journal of Neonatal Surgery, 2025)
The present government's vision "Viksit Bharat 2047," calls for India to become a fully developed country by 2047, exactly after 100 years of independence. The government of India's ambitious goal to make the country a developed nation by the year 2047, when it celebrates its centenary of independence, is embodied in Viksit Bharat@2047. Covering a wide range of development aspects, including social progress, environmental sustainability, economic prosperity, and efficient governance. This vision underscores the critical juncture at which India currently stands. India's GDP is expanding at a reasonably fast rate among global economies. It surpassed the UK to become the fifth-largest economy in September 2023 and is expected to reach the third rank by 2030. However, India ranks 142 out of 197 nations in terms of per capita income; therefore, leapfrogging the economy in the next 25 years from a lower-middle-income category to developed country status will not be an easy task. The World Bank’s definition of a developed country requires the country to have a per capita income of USD. 13205 and India with USD. 2600, will have to multiply its per capita income more than 5 times. This translates into an annual average growth of 7.5 per cent in per capita In the given global environment, the acceleration in growth for a sustained period requires a significant increase in investments .In this regard, FDI has its inevitable role to play in the growth of the country. In fact, India’s impressive growth story cannot be written without mentioning the significant role played by FDI in the past as well as in the near future in the overall process of development of the country. it is one of the most important driving forces to realise the dream of Viksit Bharat particularly in developing nations like India where domestic savings are not sufficient to achieve the goal of sustainable development and also the dream of Viksit Bharat. FDI offers the number of benefits like the overture of new technology, innovative products, and extension of new markets, opportunities for employment, and introduction of new skills, etc., which reflect in the growth of income of any nation. This chapter is an attempt to analyse the trends of FDI inflows in India, the impact of the pandemic on FDI, analyses the association between economic growth and a few challenges faced by the Indian economy in this context.